The Cardiogenic Shock with Antihypertensive Drugs Intoxication in a Child - Hatice Feray Arı; Fatih Eren; Dorukhan Besin; İbrahim Altun (Galenos Yayinevi, 2022)
Combination antihypertensive treatments are usually used in everyday life, which has a life-threatening risk of using an overdose accidentally or suicidally. The effects of calcium channel blockers on the cardiovascular system are negative chronotropic, myocardial depression, decreasing atrioventricular signals, and vasodilatation. Beta blocker drugs are affected to beta receptors of catecholamines with competitively inhibition. Hypotension and bradycardia are the most common cardiac manifestations, and the others are arrhythmias, pulmonary edema, depression of the central nervous system. A previously healthy 4-year-old boy used accidentally 240 mg verapamil/4 mg trandolapril two pieces and 5 mg nebivolol one, at the time of admission his clinical condition was in cardiogenic shock. We successfully treated him with insulin-euglycemia/glucagon treatment, calcium, and lipid infusion therapy, plasmapheresis, and continuous venovenous hemodiafiltration without any sequels. The intoxication of calcium channel blockers and beta blocker drugs are rare but severe cases because of life-threatening.